Analisis Campur Kode ke Luar (Outer Code Mixing) pada Lagu “Everybody Knew” Ciptaan Citra Scholastika - Dola, Hega Dwi Dian; Afnita, Afnita (AHKAM, 2025)
The phenomenon of code mixing in the use of Indonesian, especially in works of art such as song lyrics, is one of the factors that cause language shift in the era of globalization. This study aims to analyze the form of outward code mixing in the lyrics of the song “Everybody Knew” by Citra Scholastika. The research used descriptive qualitative method with the object of research in the form of song lyrics “Everybody Knew” published through YouTube platform. The data collection technique was carried out through the method of listening and recording, with the steps of listening to the song thoroughly, recording the parts of the lyrics that contain code mixes, and analyzing the types of code mixes that appear. Data analysis used data reduction, data presentation, and conclusion drawing models. The results showed that the song “Everybody Knew” consists of 30 stanzas with 56 lyrics, and there are seven stanzas that contain code mix from Indonesian to English. There are four forms of code-mixing found, which are then repeated four times throughout the lyrics of the song. In conclusion, the code mix in the song “Everybody Knew” shows a tendency to use foreign languages as part of the musician's artistic expression style, as well as reflecting the influence of global culture in everyday language use.